Productive Zakat as an Instrument for Business Development Strategy: An Analytical Hierarchy Process (AHP) Study in South Kalimantan Indonesia - Yusuf Asyahri; Atika Zahra; Annisa Sayyid; Annisa Mahfuzah; Faqih El Wafa; Muhammad Riza Hafizi (International Journal of Islamic Business and Economics (IJIBEC), 2025)
This study aims to identify and prioritize development strategies for Micro, Small, and Medium Enterprises (MSMEs) supported by productive zakat in South Kalimantan Province, Indonesia. Despite their significant contribution to regional economic growth, MSMEs continue to face challenges related to poverty and limited access to productive financing. Employing a descriptive–analytical approach, this study adopts a mixed-methods sequential explanatory design and applies the Analytical Hierarchy Process (AHP) to determine strategic priorities across MSME clusters. The results reveal notable differences in priority strategies among clusters. Government involvement, particularly through the National Zakat Agency (BAZNAS), is identified as the most influential factor in sustaining the MSME business ecosystem. Priority criteria include product quality improvement for Cluster I and human resource development for Clusters II and III. The preferred strategic alternatives emphasize enhancing human resource skills for Clusters I and II, while expanding market access through improved production and marketing channels is prioritized for Cluster III. These findings imply the need for cluster-based productive zakat allocation and financing schemes to strengthen zakat effectiveness as an Islamic social finance instrument.